Integrated design-system as a model of modern artistically-project processes - Skliarenko, N. (Theory and practice of design, 2016)
Essence and properties of integrated design-system (IDS) are exposed in the article, which allow to examine them as a model of artistically-project processes in contemporaneity. It is well-proven that IDS is a flexible dynamic structure, which is able to be transformed and be in harmony with nature, society and man. The multidimensionalness displays of IDS is analysed. She comes forward as an object, process, informative co-operation and space of vital functions. Their close interlacing determines integrity of the system. Properties of investigated design-system (functionality, adaptation, communicativeness, self-organization, integrity) are in-process exposed, which are important descriptions in forming of modern integrated space of design.